2006
DOI: 10.1097/01.shk.0000209545.29671.31
|View full text |Cite
|
Sign up to set email alerts
|

GLYCOGEN SYNTHASE KINASE-3β INHIBITORS PROTECT AGAINST THE ORGAN INJURY AND DYSFUNCTION CAUSED BY HEMORRHAGE AND RESUSCITATION

Abstract: Glycogen synthase kinase 3beta (GSK-3beta) is a serine/threonine protein kinase that has recently emerged as a key regulatory switch in the modulation of the inflammatory response. Dysregulation of GSK-3beta has been implicated in the pathogenesis of several diseases including sepsis. Here we investigate the effects of 2 chemically distinct inhibitors of GSK-3beta, TDZD-8 and SB216763, on the circulatory failure and the organ injury and dysfunction associated with hemorrhagic shock. Male Wistar rats were subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
42
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 26 publications
4
42
0
Order By: Relevance
“…Phosphorylation of GSK-3␤ by Akt results in inactivation of the enzyme (35). Dugo et al (45,46) have reported that GSK-3␤ inhibition protects against organ injury and dysfunction in hemorrhagic shock and endotoxemia. We speculated that increased myocardial PI3K/Akt activity in TLR4 Ϫ/Ϫ mice might result in increased phosphorylation and inactivation of GSK-3␤.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of GSK-3␤ by Akt results in inactivation of the enzyme (35). Dugo et al (45,46) have reported that GSK-3␤ inhibition protects against organ injury and dysfunction in hemorrhagic shock and endotoxemia. We speculated that increased myocardial PI3K/Akt activity in TLR4 Ϫ/Ϫ mice might result in increased phosphorylation and inactivation of GSK-3␤.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, phosphorylation of tyrosine in GSK3␣-Tyr279 and GSK3␤-Tyr216 promotes activity of GSK3␣/␤ (1,3,11,15,22,25). Importantly, GSK3␣/␤ activity is implicated in the cellular and organ response to a variety of inflammatory agents such as TNF␣ (9,25,31). ␤-catenin is constitutively phosphorylated by GSK3␣/␤ (1,3,22).…”
mentioning
confidence: 99%
“…TNF␣ is a mediator of sepsis syndrome and acute respiratory distress syndrome (9,25,31). In pulmonary microvessel endothelial cells, this laboratory demonstrated TNF causes a PKC␣-mediated barrier dysfunction associated with dislocation of ␤-catenin from ␤-actin within the zonular adherence (10,12,18,23).…”
mentioning
confidence: 99%
“…One representative data set obtained from repeated experiments is shown. endotoxemic renal dysfunction, liver injury, pancreatic injury, and neuromuscular injury, most likely by downregulating inflammatory cell infiltration, cytokine production, and expression of iNOS and CD54 through NF-kB inactivation (46)(47)(48)(49). In this study, we demonstrated that GSK-3 facilitates IFN-g-mediated Jak2/STAT1 and NF-kB activation to regulate cytokine production 5 cells/24 well) were pretreated with TDZD-8 (10 mM) for 0.5 h and then treated with Con A (25 mg/ml) or PBS for 3 h. ELISA was used to determine the total production of IFN-g. Flow cytometric analysis of IFN-g expression in NKT cells was performed by three-color staining, and the changes of IFN-g expression are shown as the fold increase as compared with the normalized PBS-treated group.…”
Section: Discussionmentioning
confidence: 99%
“…GSK-3 is negatively regulated by serine phosphorylation, mainly through the PI3K/Akt pathways; in contrast, tyrosine phosphorylation positively regulates the catalytic activity of GSK-3 via a proline-rich tyrosine kinase 2-mediated pathway (33)(34)(35). The proapoptotic and proinflammatory properties of GSK-3 have also been demonstrated in various animal models of inflammation, including experimental lung injury, shock, spinal cord trauma, arthritis, ischemia/reperfusion injury, infection, asthma, colitis, renal failure, and hepatotoxicity (36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50). GSK-3 is currently a known regulator of IFN-g signaling and is involved in IFN-g-induced inflammatory activation (51)(52)(53)(54)(55)(56)(57)(58)(59).…”
mentioning
confidence: 99%